Schizophrenia: The Dark Side of Toxoplasmosis - Eftekharian, Shahriar; Rahmati Roodsari, Sara; Arab-Mazar, Zahra; Rahimi, Mohsen (International Clinical Neuroscience Journal, 2021)
Toxoplasma gondii is an intracellular parasite that has been associated with several mental disorders. It usually causes an inapparent primary infection. Found worldwide, T. gondii is capable of infecting virtually all warm-blooded animals.1-3 Schizophrenia is a neurological disorder characterized with long-term and devastating neuropsychological problems, usually presenting in adolescents or young adults. The disease affects almost 1.1% of the global population including all races and ethnic groups with an equal prevalence in both sexes.1 T. gondii seroprevalence is strongly associated with 12-month generalized anxiety disorder but not with other anxiety, depressive, or alcohol-related disorders. Because of the intracellular nature of some parasites, their treatment and development of new drugs is a major challenge for scientists.4 Recently, the use of nanoparticles and nano-scaffolds has suggested for the treatment of parasitic diseases, although limited research has been done in this regard.5-7